2016
DOI: 10.7860/jcdr/2016/19468.7930
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Ointment as a Local Drug Delivery in the Treatment of Generalized Chronic Periodontitis - A Clinical Study

Abstract: The results demonstrate that there was significant reduction in the clinical parameters with improvement in the periodontal status on application of minocycline ointment as an adjunct to periodontal flap surgery in generalized chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Minocycline, the representative kind of tetracyclines, is active against important periodontal pathogens such as A. actinomycetemcomitans ; it also has anti-collagenase properties to reduce tissue destruction and bone resorption (Jusko et al., 2016; Olsen et al., 2017; Pokrowiecki et al., 2017). However, the commercial minocycline oniment (Perio ® , 2% dosage of minocycline ointment) inevitable enhanced the adverse effects including the retardation of bone growth, photosensitivity, permanent discoloration of developing teeth, teratogenesis, as well as hepatic and renal toxicity in susceptible individuals (Abbas et al., 2016). Besides, the generation of bacterial resistance is another major challenge that extremely restricts the benefits of minocycline in controlling infections.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline, the representative kind of tetracyclines, is active against important periodontal pathogens such as A. actinomycetemcomitans ; it also has anti-collagenase properties to reduce tissue destruction and bone resorption (Jusko et al., 2016; Olsen et al., 2017; Pokrowiecki et al., 2017). However, the commercial minocycline oniment (Perio ® , 2% dosage of minocycline ointment) inevitable enhanced the adverse effects including the retardation of bone growth, photosensitivity, permanent discoloration of developing teeth, teratogenesis, as well as hepatic and renal toxicity in susceptible individuals (Abbas et al., 2016). Besides, the generation of bacterial resistance is another major challenge that extremely restricts the benefits of minocycline in controlling infections.…”
Section: Discussionmentioning
confidence: 99%
“…The overall results associated with MIN gel revealed no significant advantage over SRD and therefore the authors suggested for further clinical trials for evaluation of its role as an adjuvant medication [ 44 ]. However, another study showed conflicting results (which demonstrated significant reduction in the clinical parameters with improvement in the periodontal status) using the same concentration of drug [ 74 ]. Furthermore, an investigation revealed that periodontal treatment with MIN gel improved the periodontal status and glycemic control with elevation of serum adiponectin in type 2 diabetic patients [ 75 ].…”
Section: General Considerations Of Various Lddsmentioning
confidence: 99%
“…It is one of the most active antibiotics against most of the microorganisms associated with periodontal disease. It has the most marked substantivity and shows greater solubility in lipids [ 11 ]. The minimum inhibitory concentration (MIC) of MH on Enterobacteriaceae, Pseudomonas , Staphylococcus and Candida isolates from periodontal pockets were 16, 128, 8 and 16 μg/mL [ 12 ].…”
Section: Introductionmentioning
confidence: 99%